Study and gesign model of smart home - سلطان الدين, علال; عبد الرحيم, عثماني; الياس, مليك; أكرم, غندير (University of El-Oued, 2022)
"This study takes place on the realization of a smart home with a remote-control system under Android application and an Arduino board. The goal of the project is to create an ideal home with high efficiency in terms of ease and precision of smart phone control, which helps the user to reduce costs and effort, taking into account the principle of comfort and safety." "تجري هذه الدراسة حول تحقيق منزل ذكي مع نظام تحكم عن بعد تحت تطبيق Android ولوحة.Arduino الهدف من المشروع هو إنشاء منزل مثالي بكفاءة عالية من حيث سهولة ودقة التحكم في الهاتف الذكي ، مما يساعد المستخدم على تقليل التكاليف والجهد ، مع مراعاة مبدأ الراحة والسلامة"
مذكرة ماستر تخصص كهروميكانيك
Keywords: Keywords: home automation. Smart home. Sensors. Arduino. M2M; أتمئة المنزل. المنزل الذكي. أجهزة الاستشعار. أردوينو. M2M .